Pemberian Bibit Ikan Kepada Petani Kampung Keranji Guguh Kecamatan Koto Gasip Kabupaten Siak - Latifa Siswati; Rini Nizar; Anto Ariyanto (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2022)
Keranji Guguh Village, Koto Gasip Subdistrict, Siak Regency is an ex-transmigration. Most of the population's livelihood is oil palm plantations. The largest area of ​​Keranji Guguh village is for plantation land. on the side of the highway Perawang – Siak. The development of lake tourism creates a lot of hope for the surrounding community, especially in terms of the economic growth of the surrounding community. Then also the social aspect of the community is better so that it can prosper the lives of the local community around it Keranji Guguh village has a lake which can be used as a fishing pond tourism object and fish-based culinary delights, but there are still few fish in the pond, so additional fish and assistance are needed. The method used to achieve the goal is by: 1) counseling. 2) training, and 3) mentoring. The results achieved after giving fish seeds and counseling to farmers have increased knowledge of 20% to 80%, the sales of tilapia can be a source of income for farmers, tilapia that is cultivated can be consumed as a source of family nutrition